Pretreatment neutrophil-lymphocyte ratio has prognosis value in breast cancer patients - Silva, Sandra Helena Kaznowski da (2022)
Objectives: This study aimed to determine the prognostic value of the pretreatment inflammatory indexes neutrophil-lymphocyte ratio, lymphocyte-monocyte ratio, and platelet-lymphocyte ratio in breast cancer. Methods: A retrospective cohort of patients with breast cancer receiving treatment at a specialized cancer hospital were collected from 2016. Pretreatment complete blood cell counts were evaluated to assess inflammatory indexes. The outcome variable was 5-year overall survival. Kaplan-Meier curves, log-rank test, and Cox regression (hazard ratio; 95% confidence interval) were used. Results: A total of 312 women (mean age 51.9 years; histopathological grade II 61.6%; tumor stage III 50.0%) were included in the study. Of these, 169 (54.2%) died within 5 years, the majority of whom had neutrophil-lymphocyte ratio ≥ 2.5 (62.5%; p= 0.002), histopathological grades II and III (60.4%; p= 0.024), more advanced tumor stages (87.7%; p<0.001), and significantly lower overall survival. Neutrophil-lymphocyte ratio ≥ 2.5 (hazard ratio, 1.53; 95% CI, 1.11-2.11) was an independent prognostic factor for overall survival. In addition, histopathological grades II (hazard ratio, 3.53; 95% confidence interval, 1.29-9.68) and III stage (hazard ratio, 2.50; 95% confidence interval, 1.45-4.34) and stage IV (hazard ratio, 6.07; 95% confidence interval, 3.43-10.73) demonstrated predictive power. Conclusion: Pretreatment neutrophil-lymphocyte ratio was considered a useful predictor of overall survival in breast cancer.